π-N Drell-Yan Process in TMD Factorization - Xiaoyu Wang; Zhun Lu (Advances in High Energy Physics)
This article presents the review of the current understanding on the pion-nucleon Drell-Yan process from the point of view of the TMD factorization. Using the evolution formalism for the unpolarized and polarized TMD distributions developed recently, we provide the theoretical expression of the relevant physical observables, namely, the unpolarized cross section, the Sivers asymmetry, and the cos⁡2ϕ asymmetry contributed by the double Boer-Mulders effects. The corresponding phenomenology, particularly at the kinematical configuration of the COMPASS πN Drell-Yan facility, is displayed numerically.